Influence of farmers’ socio-economic characteristics on nutrient flow and implications for system sustainability in smallholdings: a review - Mhoro, Lydia; Meya, Akida Ignas; Amuri, Nyambilila Abdallah; Ndakidemi, Patrick Alois; Mtei, Kelvin Marck; Njau, Karoli Nicholas (Frontiers in Soil Science, 2023)
The increase in global human population coupled with impacts of climate change has amplified the pressure on arable lands. Among others, soil fertility has been the most affected attribute. Many approaches to soil fertility management have been suggested by studies in sub-Saharan Africa (SSA), however, the question remains how sustainable these approaches are. Nutrient monitoring (NUTMON), which combine biophysical and socio-economic features for soil fertility management gives an in-situ soil fertility status of a given land use system, which ultimately provides guidance in proposing appropriate soil management techniques in a given land use system. In this review, the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) approach was deployed for systematic search of the literature materials. The review assessed different studies done on nutrient monitoring in soils of SSA to grasp the socio-economic attributes and their influence on farming systems as well as nutrient flow and balances. The review identified two most dominant smallholder farming systems in SSA; mixed crop-livestock and mixed crop farming systems. Also, this review revealed that, most nutrient balances studies in SSA have been done in mixed crop-livestock farming systems. However, regardless of the farming systems, the overall mean nutrient balances in all studies particularly of nitrogen (N) and potassium (K) were negative, indicating a significant nutrient mining. The review further revealed a vast range of biophysical soil fertility management technologies, however, their adoption have been limited with socio-economic aspects including; land ownership, gender, financial position, literacy level and access to inputs. Therefore, in view of this situation, integrating biophysical and socioeconomic disciplines could address the problem of soil nutrient depletion holistically and thus, decreasing the existing negative nutrient balances in the SSA region.